Comparative Assessment of the Anticoagulant Activity of Rivaroxaban and Dabigatran in Patients With Nonvalvular Atrial Fibrillation: A Noninterventional Study. Issue 14 (April 2016) - Tsantes, Argirios E.; Kyriakou, Elias; Ikonomidis, Ignatios; Katogiannis, Konstantinos; Papadakis, Ioannis; Douramani, Panagiota; Kopterides, Petros; Kapsimali, Violetta; Lekakis, John; Tsangaris, Iraklis; Bonovas, Stefanos
Abstract : Abstract: There is a shortage of data in everyday clinical practice about the anticoagulant effects caused by the new oral anticoagulants (NOAs). Our aim was to estimate the intensity of anticoagulant activity induced by rivaroxaban 20 mg qd and dabigatran 110 mg bid among patients with nonvalvular atrial fibrillation (NV-AF). We studied 20 patients with NV-AF treated with dabigatran, and 20 patients treated with rivaroxaban. We performed conventional coagulation tests, thrombin generation (TG) test, thromboelastometry (ROTEM), and epinephrine-induced light transmission aggregometry (LTA) in all 40 patients and 20 controls. Hemoclot Thrombin Inhibitors (HTI) and Factor Xa Direct Inhibitor (DiXaI) assay were used to measure dabigatran and rivaroxaban plasma levels, respectively. Measurements of all assays estimating anticoagulant activity across the 2 patient groups were similar, except for aPTT. Patients on dabigatran exhibited statistically significantly prolonged aPTT values ( P  < 0.001). In LTA, patients on dabigatran also showed decreased aggregation compared to those on rivaroxaban ( P  = 0.045). Regarding the TG test, there was no association between endogenous thrombin potential (ETP) and rivaroxaban plasma levels ( P  = 0.33) as opposed to dabigatran levels ( P  < 0.001), but significant correlations were observed between rivaroxaban plasma concentrations and kinetic parameters of TG assay (Tlag, P  = 0.045; Tmax, P  = 0.016; and Cmax, P  = 0.003). Based on ROTEM and TG assays, the anticoagulant effects induced by the 2 drugs given in the specific dose regimens in real-world patients were comparable. Only platelet aggregation was found to be more affected by dabigatran as compared to rivaroxaban.